2002
DOI: 10.1016/s0167-4889(02)00247-1
|View full text |Cite
|
Sign up to set email alerts
|

cDNA array reveals mechanosensitive genes in chondrocytic cells under hydrostatic pressure

Abstract: Hydrostatic pressure (HP) has a profound effect on cartilage metabolism in normal and pathological conditions, especially in weight-bearing areas of the skeletal system. As an important component of overall load, HP has been shown to affect the synthetic capacity and well-being of chondrocytes, depending on the mode, duration and magnitude of pressure. In this study we examined the effect of continuous HP on the gene expression profile of a chondrocytic cell line (HCS-2/8) using a cDNA array containing 588 wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…It is difficult to assess the individual effects of each of these potential stimuli due to the differences between experiments; however some trends do emerge from the data. Continuous loads or high frequency, high magnitude loads inhibits cell processes such as matrix synthesis and growth (Buschmann et al, 1995;Davisson et al, 2002;Fukuda et al, 1997;Sironen et al, 2002;Wu and Chen, 2000), while low magnitude dynamic loading stimulates matrix synthesis (Buschmann et al, 1995;Davisson et al, 2002;Fukuda et al, 1997;Wu and Chen, 2000). Reduced chondrocyte proliferation was also recorded in DMB immobilised chick growth plates (Germiller and Goldstein, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to assess the individual effects of each of these potential stimuli due to the differences between experiments; however some trends do emerge from the data. Continuous loads or high frequency, high magnitude loads inhibits cell processes such as matrix synthesis and growth (Buschmann et al, 1995;Davisson et al, 2002;Fukuda et al, 1997;Sironen et al, 2002;Wu and Chen, 2000), while low magnitude dynamic loading stimulates matrix synthesis (Buschmann et al, 1995;Davisson et al, 2002;Fukuda et al, 1997;Wu and Chen, 2000). Reduced chondrocyte proliferation was also recorded in DMB immobilised chick growth plates (Germiller and Goldstein, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the persistent mineralization in the bone collar surrounding the Gadd45␤ Ϫ/Ϫ growth plate, abundant tartrate-resistant acid phosphatase (TRAP)-positive osteoclast-like cells were present in the diaphyseal collar in Gadd45␤ Ϫ/Ϫ mice. 6 In contrast to Mmp-13 knock-out mice but similar to the Gadd45␤ knock-out mice, both Col10a1 knock-out mice and transgenic mice with a dominant interference Col10a1 mutation have subtle growth plate phenotypes with compressed proliferative and hypertrophic zones and altered mineral deposition (73,74). The decreased Col10a1 expression because of GADD45␤ deficiency suggests that GADD45␤ plays a role in matrix remodeling at the late hypertrophic stage The chondrodysplasia (cho/cho) mouse, which carries a loss of function mutation in the Col11a1 gene, has wider long bones and shorter length possibly because type XI collagen influences the formation of type II collagen fibrils at early stages of chondrogenesis (75).…”
Section: Discussionmentioning
confidence: 99%
“…The decreased Col10a1 expression because of GADD45␤ deficiency suggests that GADD45␤ plays a role in matrix remodeling at the late hypertrophic stage The chondrodysplasia (cho/cho) mouse, which carries a loss of function mutation in the Col11a1 gene, has wider long bones and shorter length possibly because type XI collagen influences the formation of type II collagen fibrils at early stages of chondrogenesis (75). Other ECM proteins, 6 K. Ijiri, N. Walsh, and M. B. Goldring, unpublished data. FIGURE 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The "10% cutoff " separating low-risk from high-risk disease has been confirmed by others and is reflected in the new World Health Organization (WHO) classification of myeloid neoplasms that subdivides RAEB into 2 subtypes, RAEB-1 and RAEB-2, with 10% blasts as the distinction between them. 6 The ATG trial of Molldrem et al preceded the WHO classification and the recently reported British antilymphocyte globulin (ALG) trial 7 also used the older French-American-British MDS classification, so it is not clear how refractory cytopenia with multilineage dysplasia patients (RCMD-another new WHO category 6 ) will respond to ATG/ALG compared with RA patients, nor is it known whether RAEB-1 patients might fare better than RAEB-2.…”
Section: Responsementioning
confidence: 99%